"Information Warfare" and Online News Commenting: Analyzing Forces of Social Influence Through Location-Based Commenting User Typology. (July 2017) - Zelenkauskaite, Asta; Balduccini, Marcello
While most of the online participation research assumes the Western notion of fulfilling deliberative practices, online contexts have been also found to be an active battleground for so-called information warfare. To test the potential for online comments being used by cross-national political opponents, we analyze the case of online comments on the most active Lithuanian online news portal's Russian-language edition. This news portal presents itself as a unique case, since Russia was found to engage in a support or mobilization of the compatriot community in the Baltic States by exercising "soft influence."To analyze such "soft influence" our study proposed a framework called Commenting User Typology (CUT). The CUT combines three types of data points: a) content level (topic of the story category), b) user level (frequency of posting), and c) the timing and location of the posting to contribute to studies of online social influence. We have applied the CUT framework to the commenting practices of 4, 940 users who produced 34, 038 comments over a month. In the analysis, we found that the majority of the users' posts were low in topic variety and infrequent; followed by low in variety and frequent; high in topic variety and frequent; and high in topic variety and infrequent in posting. Moreover, while around a half of the comments come from Lithuania, 16% from Russia, yet more than 7% were found to mask IP addresses. Also, the results of this study suggest that more active participants tend to participate in more topic areas and that posting occurs faster in more active topic areas. The implications of this study relate to online news portals overall as well as online news portals in the non-Western contexts or electoral totalitarian regimes as Russia. We argue that user-based analysis, such as the CUT-based approach we proposed, can be particularly relevant for contexts where deliberative practices are still in negotiation.